Ostracism affects children’s behavioral reactivity and gaze cueing of attention - Giada Basset; Alessia Testa; Chiara Turati; Ermanno Quadrelli; Hermann Bulf (PLoS ONE, 2025)
Being ostracized is a negative experience that threatens important psychological needs, inducing considerable cognitive and behavioral changes and influencing the processing of social signals such as gaze-cueing. Yet, little is known about how self-experienced ostracism affects children’s behavior and attentional processes. The present study aims to explore whether the social experience of being included or ostracized can modulate gaze-cueing of attention and behavioral reactivity in 6- (N = 40) and 10-year-old children (N = 40) and adults (N = 50). Participants were video-recorded while playing an online ball-tossing game (i.e., Cyberball), where they could be either included or ostracized. They then participated in a gaze cueing task, where the cue was provided by the eye-gaze of a central human face, and the target could appear in a congruent or incongruent position. Results revealed that ostracism affected both adults’ and children’s ability to follow another’s gaze, as they were slower to respond to incongruent targets when ostracized compared to when included. Additionally, ostracism impaired 10-year-old children’s accuracy in responding to the target. Behavioral reactivity results demonstrated that both children and adults were more disappointed during the ostracism vs. inclusion condition. Overall, current findings demonstrate that self-experienced ostracism modulates children’s and adults’ behavioral reactivity and processing of social signals such as gaze cueing.